AN ANALYSIS OF THE UTILIZING ZOOM APPLICATION TO ENGLISH LEARNERS’ SPEAKING SKILL MOTIVATION - Sabila Nur Risma (IKIP Siliwangi, 2021)
Speaking is one of the productive skills that should be learned and mastered by English learners which gives them the ability to communicate effectively in this global world. However, most learners face difficulties in learning English, especially in mastering speaking skills. The lack of motivation in learning English is the most common problem faced by learners. With the development of technology, employing Zoom Application in learning English is recommended for fun and exciting learning. This research aims to analyze how applying Zoom Application can improve English learners’ motivation to speak in English. The descriptive qualitative method is used in this research and to gain the data, the researcher used some instruments, there are questionnaires and interviews, which were carried out to 30 learners in English Zoom Club as subjects of the research. The result of this research suggested that applying Zoom Application is very interesting since it provides such motivating and stimulating activities for English learners. Moreover, using Zoom Application make English learners have an appropriate platform and new friends to practice improving their speaking skill at the same time. Keywords: Speaking Skill, Motivation in Language Learning, Zoom Application